ECO-ORIENTED TEACHING OF POLYMERS IN THE SCHOOL CHEMISTRY CURRICULUM: FROM TRADITIONAL TO BIODEGRADABLE MATERIALS - Kudritskiy V.A.; Gubenko M.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2026)
The article provides an overview of modern approaches to teaching polymers in school chemistry with an emphasis on ecological aspects and sustainable development. Both traditional and biodegradable polymers (PE, PVC, PLA, PHA, etc.) are analyzed in terms of their chemical properties, applications, and pedagogical potential. It has been proved that the inclusion of topics related to green chemistry contributes to the development of students’ environmental thinking and scientific literacy. An analysis of domestic and international sources has demonstrated the need for a systematic approach to the study of polymers in school education, integrating theoretical knowledge with practical and project-based forms of learning.
Keywords: polymers; biodegradable materials; school chemistry; sustainable development; green chemistry; environmental education; teaching methods